PENGARUH PENGELOLAAN KEUANGAN PRIBADI DAN PERILAKU KONSUMTIF TERHADAP KEPUTUSAN PENGGUNAAN QRIS DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL MEDIASI PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PALANGKA RAYA - Nabila Assyifa; Solikah Nurwati; Hilda Nur Mulyani; Rizki Alifvia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of personal financial management and consumptive behavior on the decision to use the Quick Response Code Indonesian Standard (QRIS), with financial literacy as a mediating variable among students of the Faculty of Economics and Business, Universitas Palangka Raya. This study employed an explanatory quantitative approach with a survey design. The sample consisted of 119 QRIS users selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire and analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with SmartPLS 4. The results show that personal financial management and consumptive behavior do not directly affect the decision to use QRIS, but both have a positive and significant effect on financial literacy. Financial literacy has a positive and significant effect on the decision to use QRIS and is able to mediate the effect of personal financial management on QRIS usage decisions. However, financial literacy does not mediate the effect of consumptive behavior on QRIS usage decisions. The R-square value indicates that the model explains 21.5% of QRIS usage decisions and 24.2% of financial literacy. These findings confirm that financial literacy is an important factor in encouraging QRIS usage decisions, particularly through more directed personal financial management.